Global supply chain and operations management : a decision-oriented introduction to the creation of value /: a decision-oriented introduction to the creation of value. ([2017]) - Ivanov, Dmitry, 1978-; Schönberger, Jörn; Tsipoulanidis, Alexander
No abstract available